Ghana's soya bean market - Ministry of Food and Agriculture, Ghana; International Food Policy Research Institute; Amewu, Sena; Arhin, Eunice; Danso, Jane; Doughan, Roland Ato; Nafrah, Christiana; Owusu, Ivy; Pauw, Karl (International Food Policy Research Institute, 2020)
Soya bean is an important legume that is both a valuable source of feed for livestock and fish and a good source of protein in human diets. The bean contains around 30 percent cholesterol free oil, 40 percent protein, and essential vitamins (El Agroudy et al. 2011). The soya bean industry provides numerous opportunities for value chain actors from seed and grain production through to processing and marketing. As such, growth and modernization of the soya bean sector has potential to improve livelihoods and reduce poverty. While industrial processing and utilization of soya bean has expanded in Ghana, domestic production has not kept up with demand, resulting in significant growth in imports. Currently around half of soya beans or soya bean products is imported (Eshun et al. 2018; Gage et al. 2012). Average soya bean crop yields are low, ranging from 0.7 to 1.7 metric tons per hectare depending on variety, the environment, and management practices used (SRID 2017).